Pengembangan E-Modul Menggunakan Glideapps pada Materi Pengisian Surat Pemberitahuan (SPT) Pph Badan Kelas XI Akuntansi SMK Negeri di Surabaya - Denisa Anggi Prasanti; Susanti (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
This research aims to: produce e-modules using GlideApps, describe the feasibility of e-modules using GlideApps, and determine students' responses after testing the e-modules being developed. This type of research is development research with a 4D model. The e-module developed is reviewed and validated first by material experts, language experts and media experts. Then a limited trial was carried out on 30 students in class XI Accounting at State Vocational Schools in Surabaya. The results of this research indicate that the e-module using GlideApps for filling out Corporate Income Tax Returns is suitable for use. The feasibility of the material validation results is 87.5% in the very feasible category, the feasibility of the language validation results is 96% in the very feasible category, the feasibility of the media validation results is 92% in the very feasible category, and the student response results are 97.3 % showing a positive response.